The Interplay of Biopsychosocial Determinants in Maternal Mental Health During Pregnancy: Evidence from Takalar Regency, Indonesia - Muis, Masyita; Reski, Rahayu Nurul; Hadju, Veni; Syam, Aminuddin; Indriasari, Rahayu; Rahmawati, Ros (Journal of Neonatal Surgery, 2025)
Pregnancy is an important period in a woman's life that requires special attention to physical and mental health. Stress during pregnancy can arise from various sources, which can lead to health problems including postnatal depression. This study aimed to investigate the relationship between lymphocyte levels, employment status, and stress levels in pregnant women. An observational cross-sectional study was conducted among pregnant women in Takalar Regency, South Sulawesi. A total of 60 pregnant women participated in the study. Data collection involved structured interviews using the Kessler Psychological Distress Scale (K10) and the Depression, Anxiety, and Stress Scale (DASS-42). Statistical analyses included univariate and bivariate tests, with associations assessed using the Chi-Square test. Results showed that approximately 75% of the participants were at risk of stress, and 30% were at risk of combined stress, depression, and anxiety. Bivariate analysis revealed that pregnant women working in informal sectors, particularly as housewives, were significantly more likely to experience stress compared to those in formal employment (p = 0.042). Furthermore, abnormal lymphocyte levels (either low or high) were significantly associated with increased risk of stress, depression, and anxiety (p = 0.035). These findings highlight the need for targeted mental health interventions, especially for unemployed or informally employed pregnant women and those exhibiting immunological alterations during pregnancy. Strengthening psychological support and monitoring immune function during prenatal care may help mitigate adverse mental health outcomes among pregnant women during pandemic conditions